Challenges in maritime evacuation during pre-hospital emergency anesthesia on a remote island in Indonesia: A case report - Mutiar, Airi; Arifi Abbas, Kun (Narra J, 2025)
Preeclampsia and eclampsia remain significant contributors to maternal and perinatal mortality. Managing these conditions is particularly challenging in remote areas in many islands of Indonesia, where access to medical care is severely limited. The aim of this study was to analyze the pre-hospital anesthetic management of an eclampsia patient during maritime evacuation to a higher-level facility, highlighting the complexities of medical transport in resource-limited settings. A 38-year-old multiparous woman from a remote village on Pagerungan Island, Indonesia, at 37 weeks of gestation, presented with tonic-clonic seizures consistent with eclampsia. The absence of antenatal care necessitated urgent intervention. Upon presentation, the patient had a Glasgow Coma Scale (GCS) score of 5, tachycardia, and irregular breathing, requiring rapid-sequence intubation and magnesium sulfate administration. Given the geographic constraints, the patient was evacuated by sea under challenging conditions. Despite significant waves, a multidisciplinary team successfully performed an emergency cesarean section onboard, delivering a male infant who required neonatal resuscitation. Postoperatively, both mother and neonate were transferred to a higher-level facility. However, engine failure extended the journey to 18 hours, leading to depletion of oxygen and essential medications, necessitating critical decision-making. This case underscores the significant challenges of emergency eclampsia management in remote settings, particularly during maritime evacuation. Effective stabilization, anesthesia, monitoring, and timely transport are crucial. This case highlights the need for optimized evacuation protocols and increased healthcare resource allocation to enhance maternal and neonatal outcomes in maritime and other resource-limited settings.